2005
DOI: 10.1074/jbc.m502320200
|View full text |Cite
|
Sign up to set email alerts
|

PDGF-BB Regulates p27 Expression through ERK-dependent RNA Turn-over inVascular Smooth MuscleCells

Abstract: Cyclin-dependent kinase inhibitor p27, a critical determinant for cell cycle progression, is an important regulation target of mitogenic signals during arterial injury. In this study, we show in rat aortic smooth muscle cells that PDGF-BB down-regulated p27 protein and mRNA in an ERK-dependent mechanism. Inhibition of ERK, but not other subtypes of the mitogen-activated protein kinase family, prevented the reduction of p27 protein and mRNA. Conversely, direct activation of ERK via adenovirus-mediated expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 39 publications
2
39
0
Order By: Relevance
“…The levels of p27 are high in quiescent cells and decline in response to mitogenic factor stimulation. Several studies have suggested that the Ras-ERK1/2 signaling pathway is involved in the mitogen-induced downregulation of p27 (Kawada et al, 1997;Kerkhoff and Rapp, 1997;Woods et al, 1997;Greulich and Erikson, 1998;Rivard et al, 1999;Treinies et al, 1999;Lenferink et al, 2000;Yang et al, 2000;Delmas et al, 2001;Mirza et al, 2004;Gysin et al, 2005;Sakakibara et al, 2005). In contrast, other studies failed to document any significant change in p27 levels following inhibition of ERK1/2 signaling by synthetic MEK1/2 inhibitors or dominant-negative ERK2, or after conditional activation of the pathway by activated Raf-1 or MEK1 (Sewing et al, 1997;Takuwa and Takuwa, 1997;Weber et al, 1997a;Cheng et al, 1998;Ladha et al, 1998;Chen et al, 1999;Tetsu and McCormick, 2003).…”
Section: Erk1/2 Map Kinases In Cell Cycle Control S Meloche and J Poumentioning
confidence: 93%
“…The levels of p27 are high in quiescent cells and decline in response to mitogenic factor stimulation. Several studies have suggested that the Ras-ERK1/2 signaling pathway is involved in the mitogen-induced downregulation of p27 (Kawada et al, 1997;Kerkhoff and Rapp, 1997;Woods et al, 1997;Greulich and Erikson, 1998;Rivard et al, 1999;Treinies et al, 1999;Lenferink et al, 2000;Yang et al, 2000;Delmas et al, 2001;Mirza et al, 2004;Gysin et al, 2005;Sakakibara et al, 2005). In contrast, other studies failed to document any significant change in p27 levels following inhibition of ERK1/2 signaling by synthetic MEK1/2 inhibitors or dominant-negative ERK2, or after conditional activation of the pathway by activated Raf-1 or MEK1 (Sewing et al, 1997;Takuwa and Takuwa, 1997;Weber et al, 1997a;Cheng et al, 1998;Ladha et al, 1998;Chen et al, 1999;Tetsu and McCormick, 2003).…”
Section: Erk1/2 Map Kinases In Cell Cycle Control S Meloche and J Poumentioning
confidence: 93%
“…It is well established that p27 expression is mainly posttranslationally regulated by the ubiquitin-proteasome pathway (Pagano et al, 1995;Montagnoli et al, 1999;Malek et al, 2001;Kamura et al, 2004). However, some studies demonstrate that p27 might also be transcriptionally regulated (Servant et al, 2000;Sakakibara et al, 2005). Nevertheless, at present, the mechanisms involved in such regulation remain unidentified.…”
Section: Introductionmentioning
confidence: 92%
“…However, as shown above, PDGF reduced p27 Kip1 promoter activity and mRNA abundance in Balb/c-3T3 cells, NIH 3T3 cells and MEFs examples, p27 Kip1 promoter activity declined 90% in PDGF-treated aortic smooth muscle cells, 60% in eicosanoid-treated endothelial cells, and 23% in muscle satellite cells exposed to insulin-like growth factor 1. 25,26,28 Changes in p27 Kip1 stability contributed to changes in p27 Kip1 mRNA abundance in PDGF-treated smooth muscle cells and histidine-deprived hepatoma cells 26,75,76 although not in other systems. 41,42,74 Deletion analysis of the p27 Kip1 promoter localized the PDGFresponsive element to a region approximately 600 bp upstream (or slightly downstream) of the most 3' transcription start site.…”
Section: Discussionmentioning
confidence: 99%